Glaucoma in Asia- An epidemiological perspective - Agrawal, Ajai; Singh, Anupam; Mittal, Sanjeev Kumar (Nepalese Journal of Ophthalmology, 2018)
Glaucoma is the third most common cause of global visual impairment. Bilateral blindness from glaucoma is projected to affect greater than 11 million individuals worldwide by the year 2020, with a disproportionately large number of the affected individuals being of Asian descent. The disease pattern, its response to treatment, and ground realities differ among various Asian countries. Over the past decade, there have been tremendous efforts for combating cataract blindness, but unfortunately few efforts in Asian countries have been made to establish comprehensive eye care programs in the community that include management of glaucoma. There is a need for education about the disease amongst the general public and continuing medical education and training of practicing ophthalmologists in addition to improvement of infrastructure to combat blindness due to glaucoma.